Sensitivity analysis of Wagner-Whitin algorithm - Bányai, Tamás (Journal of Production Engineering, 2023)
Material requirement planning (MRP) plays an important role in the efficiency improvement of manufacturing companies. The MRP solutions of enterprise resource planning (ERP) systems are influenced by both technological and logistics parameters, but using additional algorithms, like Wagner-Whitin or Silver-Meal heuristics, it is possible to take more parameters into consideration. These heuristics can optimise the results of MRP, especially from ordering, warehousing and transportation costs point of view. Within the frame of this article the impact of process parameters on the result of Wagner-Whitin algorithm are described.